Comparison of Four Artificial Light Technologies for Indoor Aquaponic Production of Swiss Chard, Beta vulgaris, and Kale, Brassica oleracea. Issue 5 (11th October 2017) - Oliver, Luke P.; Coyle, Shawn D.; Bright, Leigh A.; Shultz, R. Charles; Hager, Janelle V.; Tidwell, James H.
Abstract: To date, most aquaponic research has been conducted outdoors in tropical climates or in greenhouses in subtropical climates. For more northerly latitudes, aquaponic production will require supplemental light in greenhouses or insulated buildings. Two separate 3‐wk growth trials were conducted to evaluate the effects of four different lighting technologies on the growth of Swiss chard, Beta vulgaris (Trial 1) and kale, Brassica oleracea (Trial 2) in aquaponic systems. Light technologies evaluated included fluorescent (FLO), metal halide (MH), induction (IND), and light‐emitting diode (LED). Four 1175‐L systems were used with all four light types represented in each system in a complete block design. Juvenile Nile tilapia, Oreochromis niloticus (241 g) were stocked in each system and fed a floating 32% protein diet at a rate of 60 g/m 2 of plant grow space per day. In Trial 1, Swiss chard plants grown under LED lights for 3 wk achieved significantly higher ( P ≤ 0.05) average individual weights (117.7 g), higher production per unit of area (3535 g/m 2 ), and higher production per unit of energy (32.3 g/m 2 /kwh) than Swiss chard grown under the other three light types, which did not differ significantly ( P > 0.05) from each other. In Trial 2, kale grown under LED lights achieved significantly higher ( P ≤ 0.05) average individual weights (102.9 g), higher production per unit of area (2136.6 g/m), and higher production per unit of energy (381.5 g/m 2 /kwh) than kale grown under the other three light types, which did not differ significantly ( P > 0.05). The results of the two trials are in agreement and indicate that LED lights were superior to MH, FLO, and IND lights in terms of absolute plant growth as well as growth per unit of energy consumed.